Racionalidade limitada na decisão de consumo de etanol no Brasil: um estudo para o período de 2001 até 2011 - Silva, João Paulo Cabral da (2013)
Studies of ethanol consumption for light vehicles in Brazil arouses interest for researches from different parts of the world, due to the possibility of obtaining empirical results able to highlight key features of consumer behavior for this product. This dissertation proposes a study that estimates the demand equation for ethanol in Brazil in order to investigate the existence of consumption inertia that will be defined as habit in this study. An econometric model was conducted in two stages with monthly data from ANP, using instrumental variables that controlled the endogeneity in prices, to test the existence of empirical evidences of consumption inertia in consumer making decision. The states were classified in terms of ethanol-gasoline parity prices (near or far from the value of 70%) and income (rich or poor) using interaction range for these variables. The analysis was divided in two periods to capture the influence of growing fleet flex-fuel vehicles in Brazilian economy. Finally, scenarios was constructed based on moving averages (for calculating the fuel´s parity price) to understand the changes in the elasticities under the influence of stability in the states classification over time. It was concluded that there are significant differences in the values of own and cross-price elasticities between the two analyzed periods and for the different parity price ranges and income classification. The influence of inertia in the consumption decision was evidenced only for the states classified as rich, because the results captured differences in the prices elasticities magnitude only when was considered high stability criteria in time, providing evidences that short term fluctuations in ethanol prices (considering states classified as riches), in cases that significant differences in elasticities were not evidenced, comparing states classified 'in' and 'out' of the parity price range, i.e., on average, consumers in these states are able to adopt a less advantageous option (in terms of efficiency) due consumption inertia. For states classified as poor it was not observed.